Power conditioning system coupled with a flow battery for wind energy applications: Modelling and control design - Ontiveros, Leonardo Javier (2017)
Wind generation (WG) is the most widespread renewable energy resource in the world. However, this implementation inevitably leads to an increase in the problems caused by WG, e.g. frequency oscillations, power fluctuations or voltage variations. To overcome these problems, the use of a power conditioning system (PCS) coupled with a vanadium redox flow battery (VRFB) is proposed in this study. The PCS is composed of a distribution static synchronous compensator connected to a dc/dc chopper. The PCS/VRFB detailed model is presented and a three-level control system is developed. This control system allows the PCS/VRFB to perform a decoupled reactive and active power flow control. The dynamic response of the PCS/VRFB is evaluated through simulation tests, and performance characteristics of the device are obtained by means of the variation of the power references. The results obtained demonstrate that the PCS/VRFB offers a good transient response and the control system proposed allows mitigating the problems caused by wind power generation.